ANALISIS MOTIVASI BELAJAR DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS I SEKOLAH DASAR NEGERI VI BUMI NABUNG ILIR - Sari, Amalia; Aris, Ika Evitasari; Rahayu, Maulina (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the learning motivation of first-grade students in mathematics learning at SD Negeri VI Bumi Nabung Ilir. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The study focused on motivation indicators, including enthusiasm, persistence, active participation, initiative, response to rewards, focus, and achievement orientation. The findings revealed that students’ motivation was in the moderate category, characterized by fluctuating enthusiasm, inconsistent persistence, and limited active participation. Independent learning initiative was relatively low, although positive responses to rewards, focus, and achievement goals were evident in some students. Motivation increased when teachers applied concrete media, varied methods, and engaging learning approaches. It can be concluded that students’ motivation needs to be enhanced through creative, interactive, and contextual strategies so that they become more active, confident, and develop a positive attitude toward mathematics from an early stage.